The Importance of School Working Conditions for Teachers’ Job Satisfaction - Wea, Teofanne Nurinik; Mbato, Concilianus Laos (Center of Language and Cultural Studies [CLCS], 2022)
Teachers are responsible for students’ academic success and education. Therefore, their satisfaction at work needs to be observed. This study aimed to examine teachers’ job satisfaction in connection with their work intensification. It also aimed to determine the elements of the work that affected teachers’ job satisfaction, as well as how those elements were related to the qualities of the teachers. This study was undertaken involving 30 English teachers from several schools. Those schools consisted of SMAK St. Mikael Solo, SMPN Temanggung, SMAN 1 Ende, Flores and SMK Mucthyca, Ende, Flores. In conducting this study, the researchers distributed a questionnaire and interviewed the participants. Seven participants were participated in the interview section. The teachers’ job satisfaction was determined by students’ factors and school regulation. The result of the study showed that secondary school teachers were generally satisfied with their job, and rarely affected by other things such as students’ discipline and school leadership. To conclude, a school with highly satisfied teachers will provide qualified instruction and raise successful students. This study offers suggestions for schools and future researchers.